Implementation of Regents Regulations on Compulsory Madrasah Diniyah Learning in the Development of MDT Institutions. Riyadhul Jinan Pasuruan: Implementasi Peraturan Bupati Tentang Wajib Belajar Madrasah Diniyah Dalam Pengembangan Lembaga MDT. Riyadhul Jinan Pasuruan - Ahmad, Faishol; Oktavia, Renny; Churrohman, Taufiq (Proceedings of The ICECRS, 2020)
Before the enactment of the Pasuruan Regent Regulation no. 21 of 2016 concerning Compulsory Education for Madrasah Diniyah, there has been a Regional Regulation of Pasuruan Regency Number 4 of 2014 concerning the Implementation of Education which one of the contents in article 31 paragraph 2 describes the mandatory madrasah diniyah in Pasuruan. This regulation was made and determined by Mr. HM. Irsyad Yusuf, SE as the elected Regent of Pasuruan, because there is encouragement to restore the icon of Pasuruan Regency as Santri City and instill religious values in students. After 3 years this Perbup was running, it turned out to have a positive effect and impact on the Pasuruan community moreover to 1,439 Madin institutions that already existed included MDT. Riyadhul Jinan, located in Kedungboto Village, Kec. Beji Pasuruan Regency. In the second period after being re-elected as Regent, he had a superior program namely "WAK MUQIDIN" (Wayahe Kumpul Mbangun TPQ and Madin). In his remarks, Regent Irsyad said; the presence of MUQIDIN WAK will later strengthen the Madin mandatory program that has been announced since the 2016/2017 school year, and is stipulated in the form of Pasuruan Regent Regulation number 21 in 2016.